ANALISIS KEMAMPUAN BELAJAR MATEMATIKA SISWA SEKOLAH DASAR DI MASA TRANSISI PEMBELAJARAN - Luthfia Nilam Dewanti; Heru Purnomo (Institut Pendidikan Indonesia, 2022)
This research was conducted with the aims to find out how far the mathematics learning ability of elementary school students during the learning transition. The method used in this research is a qualitative descriptive research method, with the samples used as the subject of this research as many as 3 elementary school students and the sampling technique used is purposive sampling technique. Based on the results of the students' mathematics learning ability tests conducted in this research, it was found that the FR subject got a score of 96 in the very good category, the MS subject got a score of 78 in the good category, and the ZV subject got a score of 80 in the good category. The avarage score of the students’ mathematics learning ability test results in this research was 84.6. Based on this, it is known that the mathematics learning ability of elementary school students during the learning transition period is currently in the good category.